Optimizing electrostatic chuck performance through ZrO₂/Al₂O₃ ratio and doping components (SiO₂ and Y₂O₃) - Lim, Jongwoo; Kim, Dahoon; Lee, Nam Hui; Kim, Young Gon; Yu, Hak Ki; Choi, Jae Young; Park, Jae Hyuk (Ceramics International, 2025)
This study explores the enhancement of electrostatic chuck (ESC) performance through the modulation of the ZrO₂/Al₂O₃ ratio, with additional doping of Y₂O₃ and SiO₂, deposited via Atmospheric Plasma Spraying (APS). Three different ZrO₂/Al₂O₃ mixed powders, further doped with Y₂O₃ and SiO₂, were prepared and analyzed for their electrical and mechanical properties. By utilizing APS to deposit these coatings, we achieved uniform and crack-free layers with controlled thickness and consistent mechanical properties. Notably, the mixed powder with the highest ZrO₂ content achieved a relative dielectric constant of about 22 with a volume resistivity of ∼1.0 × 101⁴ Ωcm. The enhanced dielectric constant and reduced resistivity induced the Johnsen-Rahbek (J-R) effect, leading to an improved clamping force 25 gf/cm2 on glass substrate, exceeding the industrial requirement of 10∼15 gf/cm2. Additionally, this ZrO₂/Al₂O₃ composition demonstrated a breakdown voltage of approximately 4200 V and a dielectric strength of about 17 V/μm, showcasing better voltage stability compared to traditional TiO₂-doped Al₂O₃. The high breakdown strength and excellent adhesion force suggest that ZrO₂-Al₂O₃ coatings, along with Y₂O₃ and SiO₂ doping, offer superior performance and reliability, making them viable alternatives to traditional TiO₂-doped Al₂O₃ chucks in advanced semiconductor manufacturing applications.
Keywords: Atmospheric plasma spraying; Atmospheric plasma-spraying; Dielectrics property; Electrical and mechanical properties; Electrostatic chuck; Electrostatic chucks; Johnsen-rahbek effect; Mixed powder; Performance; Zro₂-doped al₂o₃; Atmospheric plasma spraying (APS); Dielectric properties; Electrostatic chuck (ESC); Johnsen-Rahbek effect; ZrO₂-doped Al₂O₃